Racial disparities in operative management of localized, non-functional pancreatic neuroendocrine tumors in surgically fit patients. Issue 2 (February 2022) - Bingmer, Katherine E.; Hue, Jonathan J.; Sugumar, Kavin; Ammori, John B.; Rothermel, Luke D.; Winter, Jordan M.; Hardacre, Jeffrey M.; Ocuin, Lee M.
Abstract: Background: Guidelines recommend resection of non-functional neuroendocrine tumors of the pancreas (NF-pNETs) that are ≥2 cm in size. We compared utilization of surgery based on race. Methods: We identified non-Hispanic White and Black patients with localized NF-pNETs ≥2 cm and Charlson-Deyo score 0–1 in the NCDB (2004–2016). We compared utilization of surgery by race, adjusting for clinicodemographic variables. Overall survival was compared based on management. Results: A total of 3459 patients were included (White = 3005; Black = 454). Black patients were younger (58vs63 years) and more often treated at academic facilities (65.3%vs60.3%). Overall, Black and White patients underwent surgery at similar rates (77.3%vs79.6%). When stratified by primary site, Black patients with body/tail tumors were less likely to undergo surgery (78.5%vs84.7%). On multivariable analysis, Black race was associated with a lower likelihood of surgery overall (OR 0.74, p = 0.034) and in patients with body/tail tumors (OR 0.56, p = 0.001). Non-operative management was associated with a higher risk of death (HR 3.19, p < 0.001). Conclusion: In a national cohort of patients with NF-pNETs meeting criteria for resection, Black race is associated with lower frequency of surgery. Operative intervention is associated with prolonged survival. Persistent racial disparities in management of a surgically curable disease should be targeted for improvement.